Selection and validation of reference genes for quantitative real-time PCR analysis under different experimental conditions in the leafminer Liriomyza trifolii (Diptera: Agromyzidae) - Chang, Ya-Wen (PLoS One, 2017)
Liriomyza trifolii is a highly-invasive leafmining insect that causes significant damage to vegetables and horticultural crops worldwide. Relatively few studies have quantified gene expression in L. trifolii using real-time quantitative PCR (RT-qPCR), which is a reliable and sensitive technique for measuring gene expression. RT-qPCR requires the selection of reference genes to normalize gene expression data and control for internal differences between samples. In this study, nine housekeeping genes from L. trifolii were selected for their suitability in normalizing gene expression using geNorm, Normfinder, BestKeeper, the ΔCt method and RefFinder. HSP21.7, which encodes heat shock protein 21.7, was used as a target gene to validate the expression of candidate reference genes. Results indicated that ACTIN and 18S were optimal for developmental stage and low temperature, TUB and 18S showed the most stable expression for sex, and GAPDH and ACTIN were the best reference genes for monitoring gene expression at high temperature. Selection and validation of appropriate reference genes are critical steps in normalizing gene expression levels, which improve the accuracy and quality of expression data. Results of this study provide vital information on reference genes and is valuable in developing a standardized RT-qPCR protocol for functional genomics research in L. trifolii.